1993
DOI: 10.1039/ft9938901783
|View full text |Cite
|
Sign up to set email alerts
|

Thermal hydrogenation of diamond surfaces studied by diffuse reflectance Fourier-transform infrared, temperature-programmed desorption and laser Raman spectroscopy

Abstract: The chemisorbed species on diamond surfaces have been studied by Fourier-transform infrared (FTIR), temperature-programmed desorption (TPD) and laser Raman spectroscopy. Oxidized diamond powders were treated thermally in an H, environment. IR spectral changes were followed during the hydrogenation of oxidized diamond powders. We observed CH bonding on diamond surfaces. The amount of CH bonding increased with the temperature of treatment below 900°C. Above 9OO"C, the amount of the CH bonding decreased. Thermall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(78 citation statements)
references
References 15 publications
6
72
0
Order By: Relevance
“…Groups with specific chemical bonds (such as hydroxyl, carbonyl, carboxylic, and epoxy) absorb light energy and is inherently illuminated with a frequency corresponding to the fundamental vibration. 87 Raman spectroscopy measures the frequencies of Raman-scattered monochromatic light. In fact, Raman spectroscopy provides sufficient chemical information, which is supplementary to FTIR.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…Groups with specific chemical bonds (such as hydroxyl, carbonyl, carboxylic, and epoxy) absorb light energy and is inherently illuminated with a frequency corresponding to the fundamental vibration. 87 Raman spectroscopy measures the frequencies of Raman-scattered monochromatic light. In fact, Raman spectroscopy provides sufficient chemical information, which is supplementary to FTIR.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…On the other hand, the surface of diamonds grown by the chemical vapor deposition (CVD) method, which can produce high quality films for practical use, has a hydrogen (H)-chemisorbed structure. It is well-known that the CVD-diamond surface can be stabilized as an H-chemisorbed structure with sp 3 hybridization [2,3]. It has been reported that hydrogenated diamonds exhibit surface electrical conductivity [4,5], and that a sub-surface hole accumulation layer in these diamonds is responsible for this phenomenon [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that hydrogenated diamonds exhibit surface electrical conductivity [4,5], and that a sub-surface hole accumulation layer in these diamonds is responsible for this phenomenon [6,7]. We previously reported that the H-chemisorption of the diamond surface gradually changed to O-chemisorption by surface oxidation based on chemical reactions at a temperature range of 300-350˚C [2,3]. The relationship between the change in the chemisorbed structures on the diamond surface and the surface conductivity has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…respectively. Figure 6 b shows the correlation between the intensity of the 810 cm 1 peak and the broad band at 1200-950 cm 1 . Similarly, Fig.…”
Section: CMmentioning
confidence: 99%
“…Four or five samples were prepared for each condition. DRIFT spectra of three different portions of the samples in the range of 4000-400 cm 1 were obtained in dry air atmosphere with no dilution. For each spectrum, 256 scans were accumulated at a resolution of 4 cm 1 .…”
Section: Introductionmentioning
confidence: 99%